Rolling Mental Accounts - Frydman, Cary; Hartzmark, Samuel M.; Solomon, David H. (Review of Financial Studies, 2018)
When investors sell one asset and quickly buy another (“reinvestment days”), their trades suggest the original mental account is not closed, but is instead rolled into the new asset. Retail investors trading on their own accounts display a rolled disposition effect, selling the new position when its value exceeds the initial investment in the original position. On reinvestment days, these investors display no disposition effect (consistent with no disutility from realizing a loss) and make better selling decisions. Using a laboratory experiment, we show that reinvestment causally reduces the disposition effect and improves trading.